Factors impacting consumers in website services: a bibliometric review in times of pandemic - Albuquerque, André Philippi Gonzaga de; Becerra, Claudia Editt Tornero; Melo, Fagner José Coutinho de; Medeiros, Denise Dumke de (Brazilian Journal of Production Engineering, 2025)
The COVID-19 pandemic has significantly boosted online shopping, compelling organizations to enhance website service quality. Since there is no prior knowledge of what satisfies consumers, this research conducts a systematic review to identify critical dimensions and attributes influencing website service quality and consumer satisfaction in a post-pandemic context. Using the Theory of Consolidated Meta-Analytic Approach (TEMAC), the review follows three structured phases: Research Preparation, Data Presentation and Interrelation, and Detailing and Model Integration. This approach integrates bibliometric principles to analyze and synthesize findings from 88 selected articles. The analysis reveals 11 key dimensions impacting website service quality: ease of use, website design/aspect, online survey, security/privacy, personalization, efficiency, system availability, reliability, information quality, responsiveness/assurance/trust, and delivery/fulfillment. The findings provide valuable guidance for organizations aiming to enhance their online service offerings. By focusing on these dimensions, businesses can formulate strategic action plans to improve consumer satisfaction, foster trust, and deliver a superior online shopping experience. This study contributes to literature by offering a comprehensive framework for understanding website service quality, supporting both academic and practical advancements in this field.
Keywords: e-services; websites; systematic review; dimensions; TEMAC